PENGARUH HARGA MINYAK MENTAH TERHADAP PENERIMAAN PERPAJAKAN DAN PAJAK PENGHASILAN DI INDONESIA - Syafrizal Syaiful (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
This research empirically analyzes the effect of oil prices on tax revenue and income tax in Indonesia. The data were collected from 33 provinces between 2016 and 2020. To analyze cross-province panel data, we used the random effect model (REM). The findings showed Indonesia's Crude Oil Price (ICP) and Brent's Crude Oil Price have a positive effect on tax revenue and are statistically significant. ICP and Brent also have a positive effect on income tax and are statistically significant. Another finding is inflation has a positive influence on tax revenue and income tax. The last finding is exchange rates have a negative effect on tax revenue and income tax in Indonesia.